Comparison of Efficiency and Sensitively between (Three Sigma, Six Sigma and Median Absolute Deviation) by using Xbar Control Chart - Hawkar Qasim Birdawod.; Dashty Ismil Jamil; Dlshad Mahmood Saleh (QALAAI ZANIST JOURNAL, 2021)
The main objective of any productivity operation is to get high quality materials and conform to the specifications so as to meet consumer desires. The quality is a principle in which some may think it is new, but it is as old as human, because the man was still in a permanent search for a good thing, and paying attention to the quality .Quality has great care in the industrialized developed countries being of economies exporter seek to control the foreign markets, scale estimators are very important in many statistical applications. The most common of scale estimators is the sample standard deviation. Standard deviation is non-robust to slight deviations from normality. The present study introduces the Comparison between another robust measure of dispersion namely Modified (Three Sigma, Six Sigma and Median Absolute Deviation) based on Shewhart mean control chart. When we compare robust methods, six sigma method have better property than the other robust methods, because control chart based on six sigma have the smallest control interval and also have the most number of out of control points.